Foliar Supplied Boron Can Be Transported to Roots as a Boron-Sucrose Complex via Phloem in Citrus Trees - Du, Wei (Front Plant Sci, 2020)
Although foliar boron (B) fertilization is regarded as an efficient way to remedy B deficiency, the mechanisms of foliar B transport from leaves to roots are still unclear. In this study, performed with 1-year-old “Newhall” navel orange (Citrus sinensis) grafted on trifoliate orange (Poncirus trifoliata) plants, we analyzed the B concentration in leaves and roots, B-sucrose complex in the phloem sap after foliar application of (10)B, girdling, and/or shading treatments. Results indicated that (10)B concentration was significantly increased in roots after foliar (10)B treatment. On the other hand, both girdling the scion stem and shading over the plants with a black plastic net significantly reduced the B and (10)B concentration in roots. LC-MS analysis revealed that foliar (10)B-treated plants had higher concentration of sucrose and some sugar alcohols in the phloem sap as compared to foliar water-treated plants. Combining with the analysis in the artificial mixture of B and sucrose, a higher peak intensity of the (10)B-sucrose complex was found in the phloem sap of foliar (10)B-treated plants compared to the control plants. Taken together, it is concluded that foliar B can be long distance transported from leaves to roots via phloem, at least by forming a B-sucrose complex in citrus plants.